Cartilage conduction as the third pathway for sound transmission. Issue 2 (April 2019) - Hosoi, Hiroshi; Nishimura, Tadashi; Shimokura, Ryota; Kitahara, Tadashi
Abstract: It has been long considered that air and bone are the two major mediators that conduct sounds to the inner ear. In 2004, Hosoi found that vibration of aural cartilage, generated by placing gently a transducer on it, could create audible sound with the same level of clarity as air- and bone-conduction sound. He thus proposed the term "cartilage conduction" for this concept. This research identified a third mediator for sound conduction to the inner ear. Hosoi also proposed the development of novel communication devices, such as hearing aids, telephones, etc. using his findings. For cartilage conduction, three sound pathways can be assumed. The transducer vibration may cause airborne sound which passes into the external auditory canal through the canal entrance (direct air pathway). Alternatively, the vibration at the cartilage may generate audible sound in the external auditory canal (cartilage-air pathway), or propagate directly to the inner ear through the skull bone (cartilage-bone pathway). A series of studies has illustrated that the cartilage-air pathway is dominant for hearing sensations in listeners with normal ears. The cartilage-bone pathway works for patients with bony aural atresia. A fourth pathway, the fibrotic-tissue pathway, is considered to act in the case of fibrotic aural atresia. In this review, we summarize this series of studies and discuss the nature of cartilage conduction.